Biodegradable polyester composition as well as preparation method and application thereof

By regulating the molecular weight of biodegradable polyester and the proportion of D-lactic acid in polylactic acid, and cooperating with compatibility agents and fillers, the problem of low lateral and longitudinal shrinkage rates of heat shrink films is solved, and high-performance heat shrink film preparation is achieved.

CN119708770APending Publication Date: 2025-03-28ZHUHAI KINGFA BIOMATERIAL CO LTD +2
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411716119.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing biodegradable heat shrinkable film has low lateral and longitudinal shrinkage, poor stability or low transparency of blown films, which limits its promotion and application in the industry.

Method used

By regulating the weight average molecular weight of the biodegradable polyester in the range of 100,000 to 170,000, the D-lactic acid proportion of polylactic acid is controlled to be 5 to 12 mol%, and combined with a compatibilizer and filler, a heat shrink film with high lateral and longitudinal shrinkage rates is prepared.

Benefits of technology

The high lateral and longitudinal shrinkage ratio of the heat shrink film is achieved, the stability and transparency of the blown film are improved, and the problem of insufficient performance of the heat shrink film in the prior art is solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to a biodegradable polyester composition as well as a preparation method and application thereof. The biodegradable polyester composition is prepared from the following components in parts by weight: 49 to 81 parts of biodegradable polyester, 20 to 50 parts of polylactic acid, 0.5 to 2 parts of inorganic filler, 0.1 to 2 parts of compatilizer and 0.1 to 2 parts of lubricant. The biodegradable polyester composition has good film blowing stability, and after the biodegradable polyester composition is prepared into a heat shrinkage film, the heat shrinkage film has good transparency, high transverse shrinkage rate and high longitudinal shrinkage rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of degradable materials, and more specifically, to a biodegradable polyester composition and a preparation method and application thereof. Background Art

[0002] Heat shrink film is a kind of packaging film that generates shrinkage force when heated to wrap the goods, thereby protecting the packaged goods.

[0003] In the prior art, the materials used to prepare heat shrinkable films are mainly polyethylene, polypropylene, polyvinyl chloride, etc., but these materials themselves are difficult to degrade naturally, which will cause serious environmental pollution. Therefore, it is urgent to develop green and environmentally friendly heat shrinkable films. Currently, biodegradable heat shrinkable films have received widespread attention, but they have not been widely promoted and applied in the industry. The main limiting factors are low transverse and longitudinal shrinkage rates and low transparency.

[0004] The PLA heat shrinkable film provided by the Chinese patent entitled "A method for preparing a PLA heat shrinkable film" has a PLA content of more than 80% and is produced by a film blowing process, but has the problem of poor film blowing stability and its transverse and longitudinal shrinkage rates are still relatively low.

[0005] The Chinese patent entitled Biodegradable Polyester Heat Shrinkable Film and Preparation Method thereof irradiates the film with electron beams, causing a certain degree of micro-crosslinking of the polyester molecular chains, thereby increasing the heat shrinkage rate. However, the increase is mainly in the longitudinal shrinkage rate, while the transverse shrinkage rate is relatively low, and the transparency is low. Summary of the invention

[0006] The primary purpose of the present invention is to overcome the problems of low transverse shrinkage and longitudinal shrinkage, poor blown film stability or low transparency of the biodegradable heat shrinkable film in the prior art, and to provide a biodegradable polyester composition.

[0007] A further object of the present invention is to provide a method for preparing the above-mentioned biodegradable polyester composition.

[0008] A further object of the present invention is to provide use of the biodegradable polyester composition in preparing a heat shrinkable film.

[0009] The above-mentioned object of the present invention is achieved by the following technical solutions:

[0010] A biodegradable polyester composition comprises the following components in parts by weight:

[0011]

[0012]

[0013] The weight average molecular weight of the biodegradable polyester is 100,000 to 170,000;

[0014] The polylactic acid is a copolymer of L-lactic acid and D-lactic acid, and the proportion of D-lactic acid repeating units is 5 to 12 mol%;

[0015] The particle size D50 of the inorganic filler is ≤6 μm.

[0016] The inventors of the present invention have found through research that by regulating the weight average molecular weight of biodegradable polyester within a specific range, the D-lactic acid ratio of polylactic acid within a specific range, and cooperating with a compatibilizer, the biodegradable polyester composition can have a high transverse shrinkage rate and a high longitudinal shrinkage rate when it is made into a heat shrinkable film. The principle is that the molecular chain of the biodegradable polyester with a specific weight average molecular weight has a suitable length, which can easily move and shrink after being heated; and controlling the D-lactic acid ratio of polylactic acid and cooperating with a compatibilizer can make the molecules of the biodegradable polyester better distributed in all directions in the biodegradable polyester composition, thereby not only improving the longitudinal shrinkage rate, but also improving the transverse shrinkage rate.

[0017] If the weight average molecular weight of the biodegradable polyester is too small, the film bubble will be severely broken during film blowing, and it is not suitable for preparing heat shrinkable films. If the weight average molecular weight of the biodegradable polyester is too large, the molecular chain is too long, and the degree of entanglement with other components is high, resulting in the inability to significantly improve the shrinkage rate. If the proportion of D-lactic acid in polylactic acid is low, it will have a negative impact on the crystallinity of the biodegradable polyester composition, thereby affecting the movement of the molecular chain of the biodegradable polyester and reducing the shrinkage rate.

[0018] In addition, the biodegradable polyester composition obtained by combining the biodegradable polyester and polylactic acid of the present invention has poor film blowing performance. On this basis, the present invention also adds a certain amount of filler and lubricant, thereby maintaining good film blowing performance while ensuring the transparency of the biodegradable polyester composition.

[0019] In the present invention, the biodegradable polyester is used as the main resin, and its content accounts for more than 45 wt % of the biodegradable polyester composition.

[0020] In the present invention, the polylactic acid can be obtained commercially or by self-production. The self-production method can be as follows: a lactide raw material containing L-lactide and meso-lactide and / or lactic acid is added to a solvent to cause a ring-opening polymerization reaction to obtain the polylactic acid.

[0021] Preferably, a lactide raw material containing L-lactide and meso-lactide is added to a solvent to undergo a ring-opening polymerization reaction to obtain the polylactic acid.

[0022] More preferably, the mass ratio of L-lactide to meso-lactide is 78-88:12-22.

[0023] More preferably, the solvent includes but is not limited to hexylene glycol.

[0024] More preferably, the ring-opening polymerization reaction is carried out in the presence of a catalyst, and the catalyst includes but is not limited to stannous octoate.

[0025] More preferably, the process of the ring-opening polymerization reaction is: first react at 130-140° C. and 1200-1400 Pa for 2-4 hours, and then react at 160-180° C. and 350-450 Pa for 4-6 hours.

[0026] In the present invention, the content of D-lactic acid in the polylactic acid can be measured by gas chromatography.

[0027] Preferably, the weight average molecular weight of the polylactic acid is 120,000 to 200,000.

[0028] The weight average molecular weight of the polylactic acid of the present invention can be measured by gel permeation chromatography.

[0029] The test process of gel permeation chromatography can be as follows: GPC uses Waters' ACQUITY APC TM The equipment was tested at a temperature of 40°C, using XT45, XT200 and XT459 columns, solvent: tetrahydrofuran, mobile phase flow rate: 0.5 mL / min. Polystyrene standards were used as standard samples, and the results were averaged three times.

[0030] In the present invention, the content of D-lactic acid units in the polylactic acid may be 5, 8, 9, 10, 12 mol%.

[0031] Preferably, the ratio of the repeating unit of dextrorotatory lactic acid (D-lactic acid) of the polylactic acid is 7-9%. The polylactic acid within the D-lactic acid content range is selected. When the obtained biodegradable polyester composition is used to prepare a heat shrinkable film, when both the transverse shrinkage rate and the longitudinal shrinkage rate are high, the transverse shrinkage rate and the longitudinal shrinkage rate are closer, thereby making the heat shrinkage performance of the heat shrinkable film better.

[0032] The biodegradable polyester of the present invention can be commercially available or homemade. The homemade method can be as follows: dibasic acid and / or its ester-forming derivatives are mixed with diol and branching agent, first reacted at 180-200° C. for 2-4 hours, a catalyst is added, and then reacted at 230-250° C. and 150-250 Pa for 4-12 hours to obtain the biodegradable polyester.

[0033] Preferably, the branching agent includes but is not limited to glycerol. The amount of the branching agent is: 0.03% to 0.05% of the mass of the dibasic acid and / or its ester-forming derivative.

[0034] Preferably, the catalyst includes but is not limited to tetrabutyl titanate. The amount of the catalyst used is 0.005% to 0.015% of the total mass of the dibasic acid and / or its ester-forming derivative and the diol.

[0035] Preferably, the molar ratio of the dibasic acid and / or its ester-forming derivative to the diol is 1:(1.05-1.2).

[0036] Preferably, the biodegradable polyester is a copolymer of a diol and a dibasic acid and / or an ester-forming derivative thereof.

[0037] More preferably, the dibasic acid is an aliphatic dibasic acid and an aromatic dibasic acid, and the molar ratio of the aromatic dibasic acid to the aliphatic dibasic acid is 1:(0.80-1.20); specifically, it can be 1:0.8, 1:0.85, 1:0.87, 1:0.90, 1:0.95, 1:1, 1:1.05, 1:1.1, 1:1.15, 1:1.16 or 1.20.

[0038] More preferably, the diol is at least one of butanediol and propylene glycol.

[0039] More preferably, the dibasic acid is at least one of an aliphatic dibasic acid or an aromatic dibasic acid.

[0040] More preferably, the aliphatic dibasic acid is C 4~10 At least one of the dicarboxylic acids.

[0041] Specifically, the C 4~10 The dicarboxylic acids are succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid.

[0042] More preferably, the aromatic dibasic acid is terephthalic acid.

[0043] Specifically, the biodegradable polyester may be at least one of polybutylene adipate terephthalate (PBAT) or polybutylene sebacate terephthalate (PBSeT).

[0044] In the present invention, the weight average molecular weight of the biodegradable polyester may specifically be 100,000, 110,000, 120,000, 130,000, 140,000, 150,000, 160,000 or 170,000.

[0045] Preferably, the weight average molecular weight of the biodegradable polyester is 100000 to 140000. When the biodegradable polyester within the weight average molecular weight range is selected, the obtained biodegradable polyester composition has higher transverse shrinkage and longitudinal shrinkage and better transparency when used to prepare a heat shrinkable film.

[0046] The weight average molecular weight of the biodegradable polyester of the present invention can be measured by gel permeation chromatography. The test process of gel permeation chromatography can be as follows: GPC uses Waters ACQUITY APC TM The equipment was tested at a temperature of 40°C, using XT45, XT200 and XT459 columns, solvent: tetrahydrofuran, mobile phase flow rate: 0.5 mL / min. Polystyrene standards were used as standard samples, and the results were averaged three times.

[0047] Preferably, the particle size D50 of the inorganic filler is 1 to 5 μm.

[0048] More preferably, the particle size D50 of the inorganic filler is 1-3 μm. When the inorganic filler with such particle size is selected, the obtained biodegradable polyester composition has higher transverse shrinkage and longitudinal shrinkage and better transparency when used to prepare heat shrinkable film.

[0049] In the present invention, the testing method of the particle size D50 of the inorganic filler can be determined by referring to the method of GB / T 19077.1-2008 "Particle Size Analysis by Laser Diffraction Method".

[0050] Preferably, the inorganic filler is at least one of talc or calcium carbonate.

[0051] In the present invention, the compatibilizer refers to a compatibilizer that can improve the compatibility of biodegradable polyester and polylactic acid.

[0052] Preferably, the compatibilizer is a copolymer containing epoxy groups.

[0053] More preferably, the compatibilizer is at least one of styrene glycidyl methacrylate copolymer or ethylene-butyl acrylate-glycidyl methacrylate copolymer.

[0054] Preferably, the lubricant is at least one of Fischer-Tropsch wax, monoglyceride, ethylene bisstearamide, oleamide or erucamide.

[0055] Preferably, the biodegradable polyester composition further comprises 0.1 to 2 parts of other auxiliary agents.

[0056] More preferably, the other auxiliary agent is at least one of an antioxidant, an antistatic agent, a UV stabilizer or a UV absorber.

[0057] More preferably, the antioxidant is at least one of antioxidant 1010 or antioxidant 168.

[0058] More preferably, the antistatic agent is at least one of ethoxylated alkyl acid amine, glycerol monostearate or ethoxylated alkyl amine.

[0059] More preferably, the UV stabilizer is at least one of 2-(2-hydroxy-3-tert-butyl-5-methylphenyl)-5-(2,4-dimethylphenyl)-2H-benzotriazol-4-one or bis(1-octyloxy-2,2,6,6-tetramethyl-4-piperidinyl) sebacate.

[0060] More preferably, the UV absorber is at least one of 2-hydroxy-4-methoxybenzophenone, 2,4-dihydroxybenzophenone, phenyl o-hydroxybenzoate or 2-hydroxy-4-n-octyloxybenzophenone.

[0061] The preparation method of the biodegradable polyester composition comprises the following steps: mixing the components, melt-extruding, and granulating to obtain the biodegradable polyester composition.

[0062] Preferably, the temperature of the melt extrusion is 160-180° C.; the screw length-to-diameter ratio of the melt extruder is 30-50:1, and the screw speed is 250-400 rpm.

[0063] The use of the above biodegradable polyester composition in the preparation of heat shrinkable films also falls within the protection scope of the present invention.

[0064] A heat shrinkable film is prepared from the biodegradable polyester composition.

[0065] Compared with the prior art, the present invention has the following beneficial effects:

[0066] The biodegradable polyester composition of the invention has good film blowing stability, and after being made into a heat shrinkable film, has good transparency, high transverse shrinkage rate and high longitudinal shrinkage rate. DETAILED DESCRIPTION

[0067] In order to more clearly and completely describe the technical solution of the present invention, the present invention is further described in detail through specific embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention. Various changes can be made within the scope of the rights of the present invention.

[0068] Some of the reagents selected in the embodiments and comparative examples of the present invention are described as follows:

[0069] Biodegradable polyester 1#: Homemade, polybutylene adipate terephthalate, the preparation method is as follows:

[0070] 3.4 kg of terephthalic acid, 3.4 kg of adipic acid, 4.6 kg of 1,4-butanediol (excess), and 3.0 g of glycerol were added to the reactor, stirred at 195°C (temperature T1) for 3 hours (time t1), and then 0.01% of tetrabutyl titanate, which accounts for the total mass of the dibasic acid and diol, was added as a catalyst, and the temperature was raised to 238°C (temperature T2), and the vacuum was turned on, the vacuum degree was 200 Pa, and the reaction was carried out for 8 hours (time t2), and the biodegradable polyester 1# was obtained. The weight average molecular weight of the biodegradable polyester 1# is 138380, and the terephthalic acid content is 47%.

[0071] Biodegradable polyester 2#: homemade, polybutylene adipate terephthalate, the preparation method thereof is different from that of biodegradable polyester 1# in that the time t1 is 2 hours and the time t2 is 4 hours. The weight average molecular weight of biodegradable polyester 2# is 107825, and the terephthalic acid content is 47%.

[0072] Biodegradable polyester 3#: homemade, polybutylene adipate terephthalate, the preparation method is different from that of biodegradable polyester 1# in that the time t1 is 4 hours and the time t2 is 12 hours. The weight average molecular weight of biodegradable polyester 3# is 156970, and the terephthalic acid content is 48%.

[0073] Biodegradable polyester 4#: Homemade, polybutylene adipate terephthalate, the preparation method is different from that of biodegradable polyester 1# in that: 3.8 kg of terephthalic acid, 3.1 kg of adipic acid. The weight average molecular weight of biodegradable polyester 4# is 134550, and the terephthalic acid content is 55%.

[0074] Biodegradable polyester 5#: Homemade, polybutylene sebacic acid terephthalate, the preparation method is different from that of biodegradable polyester 1# in that 3.4 kg of adipic acid is replaced by 5.4 kg of sebacic acid. The weight average molecular weight of biodegradable polyester 5# is 147035, and the terephthalic acid content is 47%.

[0075] Biodegradable polyester 6#: Homemade, poly(propylene glycol adipate terephthalate), the preparation method is different from that of biodegradable polyester 1# in that 4.6 kg (excess) of 1,4-butanediol is replaced by 4.5 kg (excess) of propylene glycol. The weight average molecular weight of biodegradable polyester 6# is 129802, and the terephthalic acid content is 48%.

[0076] Biodegradable polyester 7#: homemade, polybutylene adipate terephthalate, the preparation method is different from that of biodegradable polyester 1# in that the time t1 is 2 hours and the time t2 is 3 hours. The weight average molecular weight of biodegradable polyester 7# is 87952, and the terephthalic acid content is 48%.

[0077] Biodegradable polyester 8#: Homemade, polybutylene adipate terephthalate, the preparation method is different from that of biodegradable polyester 1# in that the time t1 is 8 hours and the time t2 is 16 hours. The weight average molecular weight of biodegradable polyester 8# is 196730, and the terephthalic acid content is 48%.

[0078] Polylactic acid 1#: homemade, its preparation method is as follows: PLLA / PDLA copolymer, homemade, using 88 parts by weight of L-lactide (L content ≥ 99.5%, the same below), 12 parts by weight of meso-lactide (D content is about 50%, the same below), dissolving lactide in hexanediol, adding stannous octoate, and performing ring-opening polymerization, first at a reaction temperature of 138°C and a reaction pressure of 1300 Pa for 4 hours (time t3), and then at a reaction temperature of 170°C and a reaction pressure of 400 Pa for 6 hours (time t4). Underwater pelletizing, crystallization, and drying to obtain polylactic acid 1#. The dextrorotatory lactic acid content of polylactic acid 1# is 5.8%, and the weight-average molecular weight is 187795.

[0079] Polylactic acid 2#: homemade, the preparation method is different from that of polylactic acid 1# in that the amount of L-lactide is 85 parts by weight, and the amount of meso-lactide is 15 parts by weight. The dextrorotatory lactic acid content of polylactic acid 2# is 7.6%, and the weight average molecular weight is 179672.

[0080] Polylactic acid 3#: self-made, the preparation method is different from that of polylactic acid 1# in that the amount of L-lactide is 82 parts by weight, and the amount of meso-lactide is 18 parts by weight. The dextrorotatory lactic acid content of polylactic acid 3# is 8.7%, and the weight average molecular weight is 182556.

[0081] Polylactic acid 4#: homemade, its preparation method is different from that of polylactic acid 1# in that: the amount of L-lactide is 78 parts by weight, and the amount of meso-lactide is 22 parts by weight. The dextrorotatory lactic acid content of polylactic acid 4# is 10.5%, and the weight average molecular weight is 174225.

[0082] Polylactic acid 5#: homemade, the preparation method thereof is different from that of polylactic acid 1# in that the time t3 is 2 hours and the time t4 is 4 hours. The dextrorotatory lactic acid content of polylactic acid 5# is 5.9%, and the weight average molecular weight is 136853.

[0083] Polylactic acid 6#: homemade, its preparation method is different from that of polylactic acid 1# in that: the amount of L-lactide is 92 parts by weight, and the amount of meso-lactide is 8 parts by weight. The dextrorotatory lactic acid content of polylactic acid 6# is 3.6%, and the weight average molecular weight is 184322.

[0084] Test method for the content of dextrorotatory lactic acid (D-lactic acid) in polylactic acid:

[0085] The dextrorotatory lactic acid content of polylactic acid can be specifically detected according to the following steps: 100 mg of polylactic acid sample is placed in a hydrothermal reactor, 10 ml of methanol is added, 1 drop of NaOH aqueous solution is added, and the hydrothermal reactor is sealed. The hydrothermal reactor is placed in a 150 ° C blast oven. After 60 minutes, the hydrothermal reactor is taken out and cooled to room temperature with running water. The filtered sample solution is transferred to a gas chromatograph (Agilent 8860 gas chromatograph, CP7502 chromatographic column), and the peaks corresponding to D-lactate methyl ester and L-lactate methyl ester are determined according to the retention time, and the peak areas of D-lactate methyl ester and L-lactate methyl ester are recorded. The peak area of ​​D-lactate methyl ester is divided by the sum of the peak areas of D-lactate methyl ester and L-lactate methyl ester to obtain the content of D-lactic acid in polylactic acid.

[0086] Inorganic filler 1#: talcum powder, Guangxi Longsheng Huamei Talc Development Co., Ltd., D50 is 2.5μm;

[0087] Inorganic filler 2#: calcium carbonate, Xinrong, ACC-815, D50 is 1.6μm;

[0088] Inorganic filler 3#: calcium carbonate, TECO, DY-66N36, D50 is 4.1μm;

[0089] Inorganic filler 4#: talcum powder, Aihai, 1250N6, D50 is 10.8μm;

[0090] Compatibilizer 1#: styrene glycidyl methacrylate copolymer, Jiayirong, HPC-3510P;

[0091] Compatibilizer 2#: ethylene-butyl acrylate-glycidyl methacrylate, DuPont, ELVALOY 4170;

[0092] Lubricant 1#: Lubricant, YT-90, Fischer-Tropsch wax, commercially available.

[0093] Other additives 1#: antioxidant, antioxidant 1010, commercially available.

[0094] Unless otherwise specified, the components (eg, lubricant 1#, other additives 1#) selected in each parallel example and comparative example are the same commercially available products.

[0095] The biodegradable polyester compositions provided in the embodiments and comparative examples of the present invention were blown into 20 μm films, and the performance was measured according to the following test methods:

[0096] (1) Horizontal and vertical shrinkage: Take 5 specimens with a length and width of 100 mm each, mark them in the vertical and horizontal directions, and indicate the horizontal and vertical directions. Adjust the oil bath temperature to 120°C, quickly put the specimen into the oil bath and start timing. Take out the specimen after 10 seconds, cool it to ambient temperature, test the horizontal and vertical lengths respectively, and calculate the thermal shrinkage of the specimen. Take the arithmetic mean as the measurement result; the calculation formula is as follows:

[0097]

[0098] S——thermal shrinkage, %;

[0099] L0——initial length of film, mm;

[0100] L——length after heating, mm.

[0101] (2) Transparency: in accordance with GB / T 2410-2008 “Determination of light transmittance and haze of transparent plastics”.

[0102] (3) Film blowing stability assessment: Film blowing stability assessment is performed at the following levels:

[0103] grade Evaluation Criteria 1 No abnormality in film blowing 2 The bubble shakes slightly 3 The film bubble shakes severely and breaks. 4 The film bubble is severely broken and difficult to rewind.

[0104] The biodegradable polyester composition of the embodiment and the comparative example of the present invention is prepared by the following preparation method: weighing each component according to the formula, mixing each component evenly, and then putting it into a twin-screw extruder, melt-extruding, and granulating to obtain the biodegradable polyester composition. Wherein, the temperature of the twin-screw extruder from zone 1 to zone 10 is 160°C, 170°C, 180°C, 180°C, 180°C, 180°C, 180°C, 180°C, 180°C, 180°C, and 180°C, respectively, the screw aspect ratio is 40:1, and the screw speed is 300rpm.

[0105] Examples 1 to 15

[0106] Examples 1 to 15 provide a series of biodegradable polyester compositions, the formulations of which are shown in Tables 1 and 2.

[0107] Table 1 Formulas of Examples 1 to 9 (parts by weight)

[0108]

[0109] Table 2 Formulas of Examples 10 to 15 (parts by weight)

[0110]

[0111]

[0112] Comparative Examples 1 to 5

[0113] Comparative Examples 1 to 5 provide a series of biodegradable polyester compositions, and their formulations are shown in Table 3.

[0114] Table 3 Formulas of Comparative Examples 1 to 5 (parts by weight)

[0115]

[0116] The properties of the biodegradable polyester compositions of the embodiments and comparative examples were tested according to the above-mentioned test methods. The test results are shown in Table 4.

[0117] Table 4 Performance test results of biodegradable polyester compositions of various embodiments and comparative examples

[0118]

[0119]

[0120] From Table 4, we can see that:

[0121] The transverse shrinkage of the biodegradable polyester compositions of Examples 1 to 15 are all above 25%, the longitudinal shrinkage are all above 66%, the light transmittance are all above 85.5%, the haze is all below 22.3%, and the grades of the blown film evaluation are all above grade 2, indicating that the biodegradable polyester composition of the present invention has high transverse shrinkage and longitudinal shrinkage, good transparency and good blown film stability.

[0122] The molecular weight of the biodegradable polyester added in Comparative Example 1 is too small, and the film bubble is severely broken during film blowing, which is not suitable for preparing heat shrinkable films. The molecular weight of the biodegradable polyester added in Comparative Example 2 is too large, and the transverse shrinkage and longitudinal shrinkage of the biodegradable polyester composition are low. The D content of the polylactic acid added in Comparative Example 3 is too small, and the transverse shrinkage and longitudinal shrinkage of the biodegradable polyester composition are low, and the transparency is poor. The particle size of the inorganic filler added in Comparative Example 4 is too large, and the haze of the biodegradable polyester composition is too high. Comparative Example 5 does not add a compatibilizer, and the film bubble is severely broken during film blowing, which is not suitable for preparing heat shrinkable films.

[0123] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A biodegradable polyester composition, characterized in that The composition comprises the following components in parts by weight: The weight average molecular weight of the biodegradable polyester is 100,000 to 170,000; The polylactic acid is a copolymer of L-lactic acid and D-lactic acid, and the D-lactic acid repeating unit accounts for 5 to 12 mol%; The particle size D50 of the inorganic filler is ≤6 μm.

2. The biodegradable polyester composition according to claim 1, characterized in that: The weight average molecular weight of the polylactic acid is 120,000 to 200,000.

3. The biodegradable polyester composition according to claim 1, characterized in that: The biodegradable polyester is a copolymer of a diol and a dibasic acid and / or an ester-forming derivative thereof.

4. The biodegradable polyester composition according to claim 1, characterized in that: The dibasic acid is at least one of an aliphatic dibasic acid or an aromatic dibasic acid.

5. The biodegradable polyester composition according to claim 1, characterized in that: The inorganic filler is at least one of talc or calcium carbonate.

6. The biodegradable polyester composition according to claim 1, characterized in that: The compatibilizer is a copolymer containing epoxy groups.

7. The biodegradable polyester composition according to claim 1, characterized in that: The biodegradable polyester composition further comprises 0.1 to 2 parts of other auxiliary agents.

8. The method for preparing the biodegradable polyester composition according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: mixing the components, melt-extruding and granulating to obtain the biodegradable polyester composition.

9. Use of the biodegradable polyester composition according to any one of claims 1 to 7 in the preparation of heat shrinkable films.

10. A heat shrinkable film, characterized in that: The method is prepared by using the biodegradable polyester composition according to any one of claims 1 to 7.

Citation Information

Cited By

  • Biodegradable polyester composition as well as preparation method and application thereof

    CN120158052A

  • Polyester composition as well as preparation method and application thereof

    CN121628317A